PENGARUH ELEMEN - ELEMEN STORE CHARACTERISTIC TERHADAP POSITIF EMOTION DI SOGO DEPARTEMENT STORE SURABAYA - YUDHITYA, MARIA AYU (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Today many retail businesses that have sprung up in the world business today. This makes a very fierce competition in the world retail. Retail businesses are emerging as a result of lifestyle demands society began to change. Like the case in the retail industry national where the number of retail developments in Indonesia continue to grow in rapidly as supermarkets, hypermarkets, minimarkets, and other retail continue to emerge. Environment to control or be controlled consumer then responded by consumers is the result of the formation of the characteristic shop consisting of product assortment, and the value of merchandise, salesperson's service, after sale service, facilities and atmosphere. With the relationship between the elements in the store characteristics that affect the emotional shopping then researchers took experiments in SOGO Department Store Surabaya. And of the results of research on the spread at 100 consumers who had shopped at SOGO Department Store Surabaya, and discussion are used in accordance with the hypothesis that the purpose was, it can be seen that the product assortment variable positive effect on emotion, because of the variety product will cause feelings of pleasure and relief for consumers, once goals with salesperson service, facilities, and the atmosphere is an important component that can lead to positive emotion on consumer, so attractive to consumers spending.